2012
DOI: 10.1891/0889-8391.26.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Can Positive Thinking Reduce Negative Affect? A Test of Potential Mediating Mechanisms

Abstract: Trait negative affect has emerged as a fundamental psychological dimension that can undermine mental health and well-being. Although recent evidence indicates that negative affect often declines over time, the malleable psychological mechanisms that predict these declines are not yet fully understood. The authors tested whether positive automatic thoughts (PATs) predicted negative affect through a positive relationship with self-esteem and hence an inverse relationship with negative automatic thoughts. Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Finally, less than 50% of respondents said they are looking for information about the disease in scientific articles and WHO daily reports, with the vast majority searching on social networks. We interpreted this finding as a defensive behavior against negative thinking and harmful information about the disease, which has been demonstrated to seriously correlate to anxiety disorders [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, less than 50% of respondents said they are looking for information about the disease in scientific articles and WHO daily reports, with the vast majority searching on social networks. We interpreted this finding as a defensive behavior against negative thinking and harmful information about the disease, which has been demonstrated to seriously correlate to anxiety disorders [37] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, our analysis implies that high levels of negative affect could lead to increased perceived FI. However, although this interpretation was supported by previous studies suggesting that negative affect is more likely to predict incivility rather than being an outcome of it ( Oliver et al, 2010 ), others showed that negative affect could be seen as an outcome of adverse social interaction, and not only as its predictor ( Lightsey et al, 2012 ). Although our findings support the former, given the alternative explanations, they should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 85%
“…A second concern is related to the explained variance of FI ranging between 23% and 25%. This may indicate that the model tested here can be expanded in future research by using additional variables related to personality measures, such as self-esteem, positive thinking ( Lightsey et al, 2012 ), or other variables such as power relations between students and teachers ( Alt and Itzkovich, 2018 ), and the way teachers construct the learning environment ( Itzkovich et al, 2020 ). The current study also used self-report measures.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the possibility that ATQP score reflects self‐esteem, recent data also indicate that trait PATs and self‐esteem correlate from .38 (O. R. Lightsey, 2010, unpublished data) to .61 (Lightsey, Johnson, & Freeman, 2012) and thus overlap by 14%–37%, which provides evidence that PATs are reasonably distinct from self‐esteem. Multiwave panel studies that examine and compare alternative causal directions and inclusion of measures of self‐esteem, optimism, and well‐being in future studies of the PATs × stressor interaction could help to more clearly rule out these alternative hypotheses.…”
Section: Discussionmentioning
confidence: 97%